Factors Related to the Low Visit of Posbindu PTM in Sintang Distric - Wagiran; Rudiansyah; Ria Damayanti; Sohibun; Aditya Sardi; Novin Yetiani (International Journal of Integrative Sciences, 2023)
The prevalence of non communicable disease (PTM) on Riskesdas 2018 has increased compared to 2013. The problem of high PTM and its large impact requires efforts to control PTM risk factors with PTM Posbindu activities but The number of PTM Posbindu visits still very low in. The purpose of this study  to determine the factors associated with the low number of community visits in the posbindu PTM. This research is a quantitative research with cross sectional design with a sample of 286 respondents with random sampling technique. The statistical test used the square-test with a 95% CI. The results showed education p-value =0.033, PR =1.313, knowledge p-value =0.010, PR =1.423, attitude p-value = 0.045, PR =1.326, access to health services p value =0.016, PR =1.357 , family support p-value =0.009, PR =1.383, motivation p-value =0.001, PR =1.481 with low PTM Posbindu visits. It is suggested to the government to improve supporting facilities, as well as strengthening health workers and cadres in providing optimal posbindu services